Deputy Mater saves the day! - Berrios, Frank; Cortes, Mario; Phillipson, Andy; Pixar (Firm); Walt Disney Pictures (Great britian Centum books ltd, 2018)
Mater helps Sheriff enforce the rules of the road when hot rods speed into town
"Inspired by the art and character designs created by Pixar."
At head of title: Disney Pixar Cars
2
Keywords: English stories